Each vs. jeweils: A cover-based view on distance-distributivity - Champollion, Lucas (Proceedings of the Amsterdam Colloquium, 2011)
Zimmermann (2002) identifies two kinds of distance-distributive items. The first kind (e.g. each) is restricted to distribution over individuals; the second kind (e.g. German jeweils) can also be interpreted as distributing over salient occasions. I explain this behavior by formally relating this split to the two distributivity operators proposed in the work of Link (atomic D operator) and Schwarzschild (cover-based operator), which I reformulate in a Neo-Davidsonian event-based framework.